Pengaruh Budaya Organisasi, Hubungan Kerja, Lingkungan Kerja, Kepemimpinan Dan Kompensasi Terhadap Kepuasan Kerja - Thyophoida W.S. Panjaitan (BIP's JURNAL BISNIS PERSPEKTIF, 2014)
This study examines the influence of organizational culture, labor relations, work environment, leadership and compensation to employees satisfaction John Gabriel Foundation at Kornit, Rembang. The hypothesis in this study are the organizational culture influence on employee job satisfaction, labor relations influence on employee job satisfaction, work environment influence on employee job satisfaction, leadership influence on employee job satisfaction and compensation effect on employee job satisfaction John Gabriel in Kornit, Rembang. Based on the analysis of data it can be seen that the organizational culture, labor relations, work environment and leadership had no significant effect on employee job satisfaction. While compensation significant effect on employee job satisfaction.